Home toxic gas monitoring system - HUANG JIE (2017)
The invention relates to a monitoring system, and particularly to a home toxic gas monitoring system. The home toxic gas monitoring system comprises a home monitoring node, a ZigBee module (terminal node), a ZigBee module (coordinator), a Web server, a GSM module and a monitoring terminal. The home monitoring node is connected with the ZigBee module (terminal node) through a serial port. The Web server is connected with the ZigBee module (coordinator) and the GSM module through serial ports. The monitoring terminal is connected with the Web server through Internet or GSM network. The home toxic gas monitoring system is beneficial in that the system can monitor toxic gas content in home and furthermore has a fault detection function and an emergency handling function; and the home toxic gas monitoring system can adjust the toxic gas content in home in three manners of a window manner, a fan manner and an exhaust fan manner. 本发明涉及种监控系统，具体是种家居有毒气体监控系统，它包括家居监控节点、ZigBee模块(终端节点)、ZigBee模块(协调器)、Web服务器、GSM模块和监控终端。家居监控